Conceptual art as an introduction to the production of Saudi artefacts using acrylic material - Haifa Ali Ibrahim AlHedaithy, Dr.; Nahal Abdullah Ali Alnajran, Lecturer (lark, 2023)
The research dealt with conceptual art as an introduction to the production of Saudi artefacts using acrylic material. It contained four chapters. The first chapter dealt with the methodological framework that includes the research problem, which is determined by the following question: What is the possibility of benefiting from conceptual art as an input for the production of Saudi artefacts using acrylic material? The chapter also contained the importance and hypothesis of the research, its questions, and its objectives. As for the second chapter, it includes the theoretical framework, and it came in two sections, the first on conceptual art, and the second on Saudi artifacts. As for the third chapter, it included the research procedures, as it followed the descriptive, analytical, and experimental method. As for the fourth chapter, it includes the results, the most important of which is that conceptual art is a source of plastic creativity that can be used to show the aesthetics of Saudi heritage. It also includes conclusions, the most important of which is the possibility of embodying contemporary Saudi artifacts with their plastic values, intellectual and social contents of pride and pride in the Saudi identity.   In addition to having recommendations and proposals.
Keywords: conceptual art - Artefacts - acrylic material